Case Report: Coexistence of Rosai-Dorfman disease and B-cell acute lymphoblastic leukemia in an adolescent - Jenabzadeh, Alireza; Binesh, Fariba; Shahbaz, Amir Pasha Amel; Alavi, Samin (Frontiers in Pediatrics, 2025)
Rosai–Dorfman disease (RDD) is an unusual, non-malignant proliferative disorder involving non-Langerhans cell histiocytes, characterized by a wide range of clinical presentations and distinctive atypical morphological patterns. The concurrent manifestation of acute lymphoblastic leukemia (ALL) alongside RDD is exceptionally rare. Here, we present the case of a 14-year-old male patient diagnosed with ALL who, during the consolidation phase of chemotherapy, developed multifocal bone, dural, and liver lesions, as confirmed through CT and MRI imaging. Histopathological evaluations of the bone and liver lesions identified features consistent with Rosai–Dorfman disease. To the best of our knowledge, this case represents the first reported instance of RDD co-occurring with high-risk pre-B-cell ALL in an adolescent undergoing chemotherapy. Unfortunately, the patient experienced a relapse of ALL and died due to a fungal infection. In this report, we analyze the distinct clinical features and disease progression of both conditions and offer an extensive review of relevant literature.